Penerapan Sistem Informasi Persediaan Barang pada Klinik Kesehatan - Ratnaningtias, Dwi (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
Clinics that have a systematic inventory record will always keep inventory records so that the quantity of inventory used in the clinic's operations is known. The purpose of this research is to find out the application of the information system of supply of goods in health clinics. Qualitative research methods. The results of the research are the latest regulations issued by the health minister have an important influence on the provision in hemodialysis clinics. It's seen since the introduction of the regulation that the gross profits have decreased compared to when the regulations were not in place. The increase in the hemodialysis rate claimed by BPJS has not been able to close the decline in clinical gross profits. This can happen because the supplies used by the clinic have a higher cost than the amount of claims received from the BPJS. Clinics can look for supplies that have the same quality but the prices offered by the manufacturer are lower. Clinical skills are good at following the rules. Because it's able to use a single-use dialyzer up to 100% in hemodialysis.